The role of cell adhesion molecules for navigating axons: density matters - Pollerberg, G. Elizabeth; Thelen, Karsten; Theiß, Martin; Hochlehnert, Birgit (Mechanisms of development, 2012)
Cell adhesion molecules of the immunoglobulin-super-family (IgSF-CAMs) do not only have a physical effect, mediating merely attachment between cell surfaces. For navigating axons, IgSF-CAMs also exert an instructive impact: Upon activation, they elicit intracellular signalling cascades in the tip of the axon, the growth cone, which regulate in a spatio-temporally concerted action both speed and direction of the axon. Density and distribution of IgSF-CAMs in the growth cone plasma membrane play important roles for the activation of IgSF-CAMs, their clustering, and the adhesive forces they acquire, as well as for the local restriction and effective propagation of their intracellular signals.